PENGARUH MODEL KOOPERATIF TIPE STAD TERHADAP PEROLEHAN BELAJAR SISWA PEMBELAJARAN IPS DI SEKOLAH DASAR - Nurkumalasari Nurkumalasari; Sugiyono Sugiyono; Kartono Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aimed to analyze the influence of the cooperative model type STAD towards gaining learning students learning Social Science in the elementary school the country South East Pontianak 09. The methods used in this research method of experiments with forms of research design pre-Experimental Design one group pretest posttest design. The population in this research the entire grade V primary school South East Pontianak 09 amounted to 30 students. Sample the whole grade V 30 students. Data collection techniques used were measurement. Data collecting tool in the form of multiple choice tests-shaped. The results of the data analysis resulted average pre-university test 62.13 while the average post-test 71.9. Based on the resulted of a test of normality of the data using the formula Chi Squared Gaussian data, then the test was performed with the-t obtained obtained tcount of 8.423 with ttabel for the significance level (α) = 0.05 dk = 30 – 1 = 29 amounted to 1.699. It turned out that tcount > ttabel or 8.423 > 1.699 then Ha received. From the results of the calculation of effect size gained 0.73 criteria were. So it can be concluded that the cooperative model type STAD give effect was being against the acquisition of student learning in class V State primary school 09 Pontianak. Keywords: Acquisition Of Learning, Cooperative Model Type STAD, Effect.